Board of Directors Characteristics and Financial Restatements: An Empirical Study of Indonesian Listed Firm - Ahyar Heru Wuryanto; Sri Yuni; Ricky Yunisar Setiawan; Oktobria Yusirat Asi; Muhammad Ichsan Diarsyad; Andreas Fajar Christmas; Iwan Christian (Universitas Negeri Semarang, 2025)
Purpose: The study examines the impact of key corporate board characteristics board tenure, size, independence, gender diversity, educational background, accounting expertise, and dual board appointments on the likelihood of financial restatements.Method: The study uses data from companies listed on the Indonesia Stock Exchange over the 2021–2023 period. A purposive sampling technique resulted in a sample of 640 firms. Logistic regression analysis was conducted using SPSS.Findings: The results show that a larger board and a higher proportion of independent board significantly reduce the likelihood of financial restatements, reflecting stronger governance and monitoring effectiveness. In contrast, longer board tenure and female board are positively associated with restatement incidence. Other factors, such as the presence of foreign board, higher educational, accounting expertise, and dual board positions, do not demonstrate a significant effect on restatement behavior.Novelty: Unlike previous studies that focus on particular industries, this research covers all publicly listed firms in Indonesia and emphasizes the role of individual board member characteristics in influencing financial reporting quality. By examining personal, professional, and demographic dimensions, the study offers new empirical insights into financial restatement behavior and fills an important gap in the governance literature.